2019
DOI: 10.1155/2019/2838615
|View full text |Cite
|
Sign up to set email alerts
|

A Provably Secure Biometrics-Based Authentication Scheme for Multiserver Environment

Abstract: With the rapid development of mobile services, multiserver authentication protocol with its high efficiency has emerged as an indispensable security mechanism for mobile services. Recently, Ali et al. introduced a biometric-based multiserver authentication scheme and claimed the scheme is resistant to various attacks. However, after a careful examination, we find that Ali et al.’s scheme is vulnerable to various security attacks, such as user impersonation attack, server impersonation attack, privileged inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
(76 reference statements)
0
23
0
Order By: Relevance
“…Specifically, the conclusions obtained by the BAN logic are through rigorous logic analysis, which further explains the confidentiality and credibility of the communication information. e notations and rules of the BAN logic used in the BAN logic calculation performed in this study are cited in [24,27,28,30,31,36,50,51]. e proof of our scheme is as follows:…”
Section: Formal Security Analysis By Ban Logicmentioning
confidence: 98%
See 2 more Smart Citations
“…Specifically, the conclusions obtained by the BAN logic are through rigorous logic analysis, which further explains the confidentiality and credibility of the communication information. e notations and rules of the BAN logic used in the BAN logic calculation performed in this study are cited in [24,27,28,30,31,36,50,51]. e proof of our scheme is as follows:…”
Section: Formal Security Analysis By Ban Logicmentioning
confidence: 98%
“…In 2018, Wang et al [26] proposed an evaluation framework for a two-factor authentication scheme for real-time data access in industrial wireless sensor networks and evaluated the relevant schemes. e third is three-factor authentication, which is based on passwords, smart cards, and biometrics [27][28][29][30][31][32][33][34][35][36][37][38][39]. In a public channel, an attacker may eavesdrop, modify, or replay transmitted messages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al [19] pointed out the scheme devised by Kumari et al is insecure against the server-impersonation Attack and presented an authentication scheme for the MSE environment. Ali et al [20] devised an AKE based on ECC for MSE and thereafter, Wang et al [21] demonstrated that the scheme proposed by Ali et al can not withstand privileged insider attack, user/server impersonation attack, DoS attack, and fails to provide forward-secrecy. Challa et al [22] devised an ECC based AKE scheme, which is unprotected against various security attacks.…”
Section: Related Workmentioning
confidence: 99%
“…An authentication protocol is indispensable to prevent unauthorized access and protect the sensitive data and user privacy. From the first smart card-based authentication protocol [7] introduced by Yang and Shieh in 1999, there have been a large number of enhanced schemes proposed [2,[8][9][10][11][12][13]. Based on the authentication factors the user employs, the authentication schemes are divided into two-factor authentication schemes and three-factor authentication schemes.…”
Section: Introductionmentioning
confidence: 99%